Exploring the relationship between water scarcity on food and nutritional security in rural households in the Nqgeleni location, Eastern Cape - Dotse, Laura Novienyo Abla (My University, 2016)
After several years of political and economic successes made since 1994, South Africa continues to experience major challenges in water availability, increased poverty, high levels of unemployment and more recently, steep increases in food and fuel prices. The Eastern Cape Province of South Africa is one of the regions that have been negatively affected by changes in climate variability, thereby, increasing the vulnerability and subjecting a significant number of households to increased poverty; water scarcity and food insecurity. The situation continues and there is a need to address this. This study sought to understand how the local households in the Eastern Cape Province in Nqgeleni location adapt to the extreme drought which impacts on their livelihood by exploring the different adaptive measures or systems that are implemented to cope with the climatic conditions in uplifting and providing food and nutrition security for sustainable growth and development. The primary aim of this research was thus to investigate how water scarcity influences food and nutritional security on rural household in Nqgeleni location. To achieve this aim, three secondary objectives were formulated. Firstly, to establish the relationship between water scarcity on food and nutritional security of rural households in Nqgeleni location. Secondly, to identify the drivers of water scarcity in the area. Lastly, to create an inventory of coping mechanism employed by rural households with water scarcity, food and nutritional security. An extensive literature review was undertaken to integrate prior findings and theories on water scarcity, food and nutritional security. The literature study revealed that water scarcity has a significant impact on food security. In addition, several factors such as demographic profile variables (population growth) and structural inefficiencies (infrastructure and management) were identified as potential drivers of water scarcity. In order to address the objectives set for this study, a number of items were sourced from the literature and a structured questionnaire administered to respondents who were selected by means of a simple random sampling technique. Data was collected from 111 usable questionnaires. The mixed method approach was employed as a core research methodology. The responses obtained were subjected to statistical analyses. Cronbach-alpha coefficients were calculated to confirm the internal consistency of the measuring instrument. The findings from this study are thus as follows. There was a significant relationship between water scarcity, food and nutritional security. Food security also has an impact on nutritional security. In addition, the drivers of water scarcity found in this study includes population growth, lack of infrastructure and poor management of water related issues by the municipality; all of which confirm findings in other studies. Furthermore, a number of respondents profile variables were identified as contributing factors to poverty, vulnerability, water scarcity, food and nutritional security in the Nqgeleni location. This includes lack of education, size of the household, and income level of the household. Based on the above findings, an inventory of coping mechanism was recommended to assist the rural households deal with water scarcity, food and nutritional security. This study has added to the empirical body of water scarcity, food and nutritional security in South Africa and the world at large. KEYWORDS: Water scarcity; Food security; Nutritional security; Eastern Cape; Nqgeleni location; South Africa
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2016.
Keywords: Nutrition--Eastern Cape; Food security--Eastern Cape--Nqgeleni; Water-supply, Agriculture; Water-supply, Rural